2019
DOI: 10.1556/2006.7.2018.137
|View full text |Cite
|
Sign up to set email alerts
|

Giving room to subjectivity in understanding and assessing problem gambling: A patient-centered approach focused on quality of life

Abstract: Background and aims: Problem gambling is characterized by high stigma and self-stigma, making relevant measurement of the burden of the disorder complex. The aim of our qualitative study was to describe healthrelated quality of life (HRQOL) impacted by problem gambling from the patients' perspective. Methods: We conducted 6 focus groups with 25 current or lifetime at-risk problem gamblers to identify key domains of quality of life impacted by problem gambling. A content analysis from the focus groups data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In line with available literature, we found a significant relationship between several mental health symptoms and being a gambler before COVID-19 lockdown, including consuming psychotropic drugs (Potenza et al, 2019), reporting a low quality of life (Bonfils et al, 2019), low sleep quality (Parhami et al, 2012), depressive symptoms (Potenza, Xian, Shah, Scherrer, & Eisen, 2005;Quigley et al, 2015) and anxiety symptoms (Bonfils et al, 2019). The same mental health indicators were also associated with increasing gambling activity during lockdown.…”
Section: Discussionsupporting
confidence: 89%
“…In line with available literature, we found a significant relationship between several mental health symptoms and being a gambler before COVID-19 lockdown, including consuming psychotropic drugs (Potenza et al, 2019), reporting a low quality of life (Bonfils et al, 2019), low sleep quality (Parhami et al, 2012), depressive symptoms (Potenza, Xian, Shah, Scherrer, & Eisen, 2005;Quigley et al, 2015) and anxiety symptoms (Bonfils et al, 2019). The same mental health indicators were also associated with increasing gambling activity during lockdown.…”
Section: Discussionsupporting
confidence: 89%
“…The other studies found mental sub-score significantly associated with gambling but no significant results regarding physical, bodily pain, vitality or general health sub-scores (Black et al, 2013;Mason and Arnold, 2007;McIntosh et al, 2016;Morasco and Petry, 2006;Najavits et al, 2010;Scherrer JF et al, 2005). Previous studies focused on harms caused by gambling (Commission, 2010;Langham et al, 2015) or on HRQOL areas impacted by gambling (Bonfils et al, 2019). Bonfils et al (2019) aimed to describe HRQOL impacted by problem gambling from a patients' perspective, through a qualitative study.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the harm experienced in a unified manner may provide an appropriate way forward. The harm caused by gambling can be assessed with subjective outcomes, such as quality of life, as opposed to the measurement of symptoms ( Bonfils et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%